Efficacy and safety of trastuzumab deruxtecan in Chinese patients with HER2-positive and HER2-low advanced breast cancer: a multicenter, observational, real-world study - Die Sang; Yanfang Su; Yurong Zhang; Yanfeng Guan; Shanmin Fan; Jintao Zhang; Lijun Zheng; Yanling Wang; Ying Guo; Zixuan Lei; Man Li; Peng Yuan (Therapeutic Advances in Medical Oncology)
Objective: Limited real-world efficacy and safety data exist regarding the use of trastuzumab deruxtecan (T-DXd) in the Chinese population with human epidermal growth factor receptor (HER2)-positive and HER2-low advanced breast cancer (BC). This multicenter, observational, real-world study aimed to evaluate the efficacy and safety of T-DXd for the treatment of Chinese patients with HER2-positive and HER2-low advanced BC. Methods: The medical records of 61 patients were collected from The Second Hospital of Dalian Medical University, Beijing Chaoyang District Sanhuan Cancer Hospital, Beijing Jingxin Hospital, and Cancer Hospital of the Chinese Academy of Medical Sciences. The primary endpoint of the study was progression-free survival (PFS), and the secondary endpoints were overall survival (OS), objective response rate (ORR), disease control rate (DCR), time to response (TTR), and safety. PFS and OS were analyzed using the Kaplan–Meier method and log-rank test. Results: The primary endpoint, PFS was 10.51 months (95% confidence interval (CI), 3.02–NE) in the HER2-low group and 10.18 months (95% CI, 3.88–NE) in the HER2-positive group. Regarding the secondary endpoints in the HER2-low and HER2-positive groups, OS data were immature, ORR rates were 37.93% and 62.50%, DCR rates were 79.31% and 87.50%, and the median TTR rates were 1.28 and 1.31 months, respectively. In the subgroup analysis, front-line treatment with T-DXd was associated with increased beneficial effects. The primary adverse events (AEs) related to T-DXd treatment were gastrointestinal reactions and bone marrow suppression, which were predominantly grades 1–2, with no severe grade 4/5 AEs reported, only one patient developed infectious pneumonia. Conclusion: This study was the first multicenter, real-world study of T-DXd for advanced BC in China. The findings demonstrated that T-DXd may be an effective antitumor treatment with controllable adverse reactions in patients with advanced BC irrespective of HER2 expression levels.